Strategi Pemasaran Asuransi Syariah dengan Teknologi Media Sosial Instagram - Pradania, Syakira; Ilham, Muhammad Luthfi Hafidh; Maolida, Nurul (Journal of Islamic Economy and Community Engagement, 2024)
This research departs from the idea that the development of information technology has had an impact on people’s lives and spurred the advancement of new ways of life in the digital era. Social media is present as a fast way of promotion (marketing) because it facilitates getting information and interacting easily, the right marketing strategy to achieve marketing goals. Public awareness about the future is still low, if you look at the future, the role of insurance is very important for the community, such as anticipating unexpected events. Islamic insurance is here to support people’s lives. This study aims to determine the marketing strategy carried out through Instagram social media. This study uses a descriptive approach that is connected directly through social media, the data source obtained from previous research studies. Based on the results of the study it can be concluded that social media is often used to market products, one of which is sharia insurance, with a product introduction marketing strategy through social media.